Analisis Dampak Penerapan Pajak UMKM Final terhadap Kepatuhan Wajib Pajak - Wira Yudha Alam; Rena Oktavianti Maghfiroh; Vivi Amelia; Christiano Yhuga Pamungkas (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economic development, particularly in job creation, income distribution, and tax revenue contribution. To support MSMEs and encourage formal tax participation, the government issued Government Regulation (PP) No. 23 of 2018, which reduced the Final Income Tax (PPh Final) rate from 1% to 0.5% of gross turnover. This policy aims to increase tax compliance, reduce administrative burdens, and expand the national tax base. This study analyzes the impact of the implementation of the Final Income Tax policy on MSME taxpayer compliance, focusing on reporting and payment behavior. The findings indicate that the tax rate reduction positively influences compliance levels among MSME taxpayers. However, several challenges persist, including limited understanding of tax procedures, lack of socialization, and low digital literacy related to tax systems. Therefore, beyond lowering tax rates, continuous education, mentoring, and the enhancement of digital-based tax services are necessary to strengthen voluntary compliance. This policy is considered a strategic initiative in improving Indonesia’s tax system and supporting sustainable economic growth driven by the MSME sector.